Integration of Sharia Economic Principles and Ecological Economic Approaches in Oil Palm Plantation Management - Wahyuni, Desi; Setiawan, Agus; Muslimin, Ahmad; Aji, Didik Kusno; Nawawi, Muhamad Anwar (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2025)
Palm oil plantations have become a major component of the economy in tropical countries, but their impact on the environment and economy often leads to various problems. In Tulang Bawang, Lampung, the Mekar Indah Jaya Farmer Group faces challenges in managing palm oil plantations, particularly regarding the use of chemical fertilizers that harm the environment and add economic burdens. This study aims to explore the integration of Islamic economics principles and ecological economics approaches in palm oil plantation management to enhance social, economic, and environmental sustainability. The research method used is qualitative, with in-depth interviews, focus group discussions (FGDs), and participatory observation, aimed at gaining insights into the application of Islamic economics principles and ecological economics in palm oil plantations. The results indicate that the use of organic fertilizer from palm waste, managed in an environmentally friendly manner, reduces dependence on chemical fertilizers, improves crop yields, and minimizes negative impacts on the soil and ecosystem. Furthermore, the integration of Islamic economics principles such as justice, sustainability, and cooperation also enhances the welfare of farmers and empowers the surrounding community. This study recommends the development of policies that integrate Islamic economics and ecology to create more sustainable farming practices.